(untitled) (World Bulletin of Management and Law, 2022)
This article discusses the constitutional and legislative foundations of the equality of women and men in Uzbekistan. In particular, it analyzes the consolidation of gender equality in the constitutions of foreign countries,provides information on the introduction of a new institution of Gender and Legal Expertise into the national rule-making process, considers the relationship of this institution with others tools such as public consultations, regulatory impact assessment, systematization of legislation